Pleomorphic Adenoma of Hard Palate: A Case Report - Dhakal, Prajwal; Regmi, Pradeep Raj; Bhattachan, Sushma; Paneru, Manisha (Journal of Institute of Medicine Nepal, 2024)
Pleomorphic adenoma is a benign and most common tumor of both major and minor salivary glands. Majority of the minor salivary glands’ tumor are malignant. However, pleomorphic adenoma is the most common neoplasm of palate. Large pleomorphic adenoma in palate may cause pressure erosion of palate mimicking malignant pathology. Imaging with Computed tomography or Magnetic Resonance Imaging is important for surgical planning of the tumors in the uncommon location like palate. Here, we present a case of histopathologically proven pleomorphic adenoma of palate which was evaluated with CT scan prior to wide local excision.